The FOMO Phenomenon on IPO Stocks: Evidence from The Indonesia Stock Exchange - Muhammad Ilham Sofyan; Fahrul Imam Santoso (GOVERNORS, 2026)
This study aims to empirically examine the effect of Underpricing and Trading Volume Activity (TVA)—acting as a proxy for the psychological bias of Fear of Missing Out (FOMO)—on the Cumulative Abnormal Return (CAR) of Initial Public Offering (IPO) stocks. Conducted on the Indonesia Stock Exchange with a six-month post-listing observation window, this quantitative research utilized a purposive sampling technique to select 42 IPO companies from 2024 to 2025. The secondary data were analyzed using Multiple Linear Regression, supported by classical assumption tests. Partial testing reveals that Underpricing has no significant effect on CAR, indicating that initial cheap price signals are merely short-term anomalies that fade as information asymmetry decreases. Conversely, TVA demonstrates a significant negative effect on CAR. This confirms that extreme trading volumes, driven by irrational FOMO and herding behaviors among retail investors, lead to severe overvaluation and subsequent medium-term underperformance. Furthermore, the simultaneous test proves that Underpricing and TVA collectively have a significant impact on CAR. These findings provide novel empirical evidence supporting Behavioral Finance theory, highlighting that early transaction euphoria strongly predicts medium-term performance declines as markets correct toward their fundamental values.